2010
DOI: 10.1016/j.brainresbull.2009.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of naltrexone facilitates reepithelialization of the cornea in diabetic rabbits

Abstract: Delayed corneal re-epithelialization is a complication of diabetes, and may lead to ulcers and erosions, which cause ocular morbidity and visual loss. This study examined the efficacy of naltrexone (NTX), a long-acting, potent opioid antagonist, applied topically, to facilitate the repair of standarized corneal abrasions in diabetic (alloxan-induced) New Zealand white rabbits (glucose levels). NTX at a concentration of 10 −4 M, or sterile vehicle (SV), was administered topically 4 times per day for 7 days to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 46 publications
0
31
0
1
Order By: Relevance
“…However, apoptosis and necrosis levels were similar (4). Naltrexone topically treated diabetic rabbits had residual corneal defects that were 23% smaller than diabetic rabbits (5).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, apoptosis and necrosis levels were similar (4). Naltrexone topically treated diabetic rabbits had residual corneal defects that were 23% smaller than diabetic rabbits (5).…”
Section: Introductionmentioning
confidence: 84%
“…HMSC were trypsinized and washed twice with PBS. A total number of 1×10 5 HSC were used for each run. To evaluate the HSC marker profile, cells were incubated in 100 μl of PBS with 3 μl of CD34-FITC for 20 min at room temperature.…”
Section: Flow Cytometry (14)mentioning
confidence: 99%
“…Naltrexone, systemically or topically administered, at high dosages can reverse and restore these defects [e.g., 55,[57][58][59][60][61][62][63][64].…”
Section: Continuous Ogfr Blockade: Enhanced Cell Proliferationmentioning
confidence: 99%
“…A comprehensive series of investigations have been conducted on the role of the OGF-OGFr axis to repair ocular surface abnormalities [51][52][53][54][55][56][61][62][63][64]. Corneal surface integrity maintains the required barrier to enable vision.…”
Section: Continuous Ogfr Blockade: Ocular Surface Wounds and Dry Eyementioning
confidence: 99%
“…In addition to these various treatment options, experimental treatments specific to diabetic keratopathy include topical administration of insulin [14], a galactose reductase inhibitor [15], or naltrexone [16]. Furthermore, we have previously shown that eyedrops containing the substance P-derived peptide FGLM-NH 2 plus IGF-1 [17] or PHSRN [18] facilitated corneal epithelial wound closure in diabetic rats.…”
Section: Introductionmentioning
confidence: 99%